Islamic Work Ethics, Employee Response, and Job Satisfaction: An Exploration of Indonesian Islamic Banking Employees - Astuti, An Ras Try (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This quantitative study investigates the impact of Islamic work ethic on employee response and job satisfaction within the Indonesian Islamic banking sector. It contributes to the academic literature by examining the nuanced relationships among these variables, shedding light on organizational dynamics specific to Islamic banking contexts. This study investigates survey responses from 120 Islamic banking employees by employing partial-least-square structural-equation modeling (PLS-SEM). Our findings indicate a significant positive influence of Islamic work ethic on both employee response and job satisfaction. We uncover the mediating role of job satisfaction in the relationship between Islamic work ethic and employee response, providing valuable insights for human resource management practices in Islamic banking environments.